Party Rules? - Gauja, Anika; Sawer, Marian (ANU Press, 2016)
"Trust in political parties has never been lower, but we have more and more of them, to the point where voters need magnifying sheets to read ballot papers. What is the relationship between party regulation and the nature of our democracy? How is it that parties have been able to gather so many public resources yet with so little scrutiny of their affairs? This is the first book on party regulation in Australia. It covers a wide range of issues, from party donations to candidate selection, from expectations of parties in a representative democracy to the reluctance to regulate and the role of the courts where legislators fear to tread. 'The regulation of political parties is one of the most important, but unexplored areas of Australian electoral policy. This important book fills that gap in providing a stimulating and insightful analysis of the pitfalls and potential solutions in this area.' - Professor George Williams AO"